Keterampilan Guru Berkomunikasi Dalam Mengajar Anak Usia Dini Di TK Negeri Pembina Tembilahan - Munawaroh, Faridatul; Sutrianingrum, Sutrianingrum; Khairi, Khairi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The process of teaching and learning between teachers and students is a form of communication. Communication has a very important role in the teaching and learning process in the classroom, because without communication the teaching and learning process does not run well, so what is the goal of education will not be achieved. The purpose of this study was to find out how the teacher's communication skills in teaching early childhood in Tembilahan State Kindergarten? What are the factors that influence communication skills in teaching early childhood at Tembilahan State Kindergarten? The subjects studied were 4 teachers. The approach that the researcher used was descriptive qualitative, the data collection method was by interview, the results of the discussion of the research on teacher communication skills in teaching early childhood in Tembilahan State Kindergarten were well implemented. Factors that affect communication skills include: situation and condition of students, facilities and infrastructure. The population factors are: teacher vocabulary, teacher knowledge and experience